Clinical outcomes of uninterrupted embryo culture with or without time-lapse-based embryo selection versus interrupted standard culture (SelecTIMO): a three-armed, multicentre, double-blind, randomised controlled trial. Issue 10386 (29th April 2023) - Kieslinger, D C; Vergouw, C G; Ramos, L; Arends, B; Curfs, M H J M; Slappendel, E; Kostelijk, E H; Pieters, M H E C; Consten, D; Verhoeven, M O; Besselink, D E; Broekmans, F; et al.
Summary: Background: Time-lapse monitoring is increasingly used in fertility laboratories to culture and select embryos for transfer. This method is offered to couples with the promise of improving pregnancy chances, even though there is currently insufficient evidence for superior clinical results. We aimed to evaluate whether a potential improvement by time-lapse monitoring is caused by the time-lapse-based embryo selection method itself or the uninterrupted culture environment that is part of the system. Methods: In this three-armed, multicentre, double-blind, randomised controlled trial, couples undergoing in-vitro fertilisation or intracytoplasmic sperm injection were recruited from 15 fertility clinics in the Netherlands and randomly assigned using a web-based, computerised randomisation service to one of three groups. Couples and physicians were masked to treatment group, but embryologists and laboratory technicians could not be. The time-lapse early embryo viability assessment (EEVA; TLE) group received embryo selection based on the EEVA time-lapse selection method and uninterrupted culture. The time-lapse routine (TLR) group received routine embryo selection and uninterrupted culture. The control group received routine embryo selection and interrupted culture. The co-primary endpoints were the cumulative ongoing pregnancy rate within 12 months in all women and the ongoing pregnancy rate after fresh single embryo transfer in a good prognosis population. Analysis was by intention to treat. This trial is registered on the ICTRP Search Portal, NTR5423, and is closed to new participants. Findings: 1731 couples were randomly assigned between June 15, 2017, and March 31, 2020 (577 to the TLE group, 579 to the TLR group, and 575 to the control group). The 12-month cumulative ongoing pregnancy rate did not differ significantly between the three groups: 50·8% (293 of 577) in the TLE group, 50·9% (295 of 579) in the TLR group, and 49·4% (284 of 575) in the control group (p=0·85). The ongoing pregnancy rates after fresh single embryo transfer in a good prognosis population were 38·2% (125 of 327) in the TLE group, 36·8% (119 of 323) in the TLR group, and 37·8% (123 of 325) in the control group (p=0·90). Ten serious adverse events were reported (five TLE, four TLR, and one in the control group), which were not related to study procedures. Interpretation: Neither time-lapse-based embryo selection using the EEVA test nor uninterrupted culture conditions in a time-lapse incubator improved clinical outcomes compared with routine methods. Widespread application of time-lapse monitoring for fertility treatments with the promise of improved results should be questioned. Funding: Health Care Efficiency Research programme from Netherlands Organisation for Health Research and Development and Merck.